UJI VALIDITAS TES MINAT INDONESIA KOMPONEN ILMU KESEHATAN DENGAN SKALA SIKAP TERHADAP PELAJARAN - Periantalo, Jelpa Jeps; Iranda, Agung; Fadzlul, Fadzlul (Psikoislamedia: Jurnal Psikologi, 2019)
The purpose of the research to conduct a external criterion related validity of Health Sciences Component of Indonesian Interest Test. Attitude toward Subject scale as an external criterion with a good psychometric properties. The subjects consisted of new students faculty of medicine and health sciences The University of Jambi N=461. There was a positive relationship with Biology рxy= 0.173 (p=0.001;p<0.05) and Chemistery рxy= 0.148 (p=0.001;p<0.05). There was a negative correlation with Economics рxy= -0.112 (p=0.016; p<0.05), Sociology рxy=-0.161 (p=0.001; p<0.05), Geography рxy=-0.171 (p=0.001; p<0.05). There was no correlation with Religion, Civics, Indonesian, English, Mathematics, Physics and History. IIT was supported with criterion related validity, it had a high power to diagnosis student interest. It could be used for high school majoring, university majoring and learning material. The next research to conduct group validity with university program and personality.